Conservation equity for local communities in the process of tourism development in protected areas: A study of Jiuzhaigou Biosphere Reserve, China. (December 2019) - Wang, Weiye; Liu, Jinlong; Innes, John L.
Highlights: Progress toward more equitable conservation practices have been tracked. Governments' equity perceptions change over time and across development stages. Distribution equity is easier to achieve than participation or recognition equity. Equity-promotion policy is restricted when it is implementing by local government. Abstract: China has built a large Protected Areas (PA) system with more than 2700 PAs. This has occurred in a modern, industrialized economy in a highly populated country, and the designation of PAs has had significant impacts on local people. Equitable sharing of responsibilities and benefits arising from biodiversity conservation with local/indigenous people is important, especially for countries such as China, which has millions of people living in and around PAs. This paper seeks to understand the notion of conservation equity and demonstrate how it works in practice. Perceptions of conservation equity changed over time and across development stages, where variance in the economic activity of locals (agriculture to tourism), state control, degree of input from locals, and local government implementation was observed. In order to achieve conservation equity, policymakers often recognize three aspects of equity: distribution equity, participation equity, and recognition equity. This study examines these notions of equity among the different stakeholders (central government, local government, and local people) during the process of PA establishment and tourism development. It focuses on four villages in Jiuzhaigou Biosphere Reserve (JBR) in China during three different periods of development. Interviews with local residents, village leaders, and government officers were conducted. Distribution equity was identified by participants as the most important of the three equities. Policies created by the central government usually address equity issues, but when these policies are implemented by the local government, equity is sometimes ignored. When local people engage in specific direct actions to improve their livelihood, they are able to better pursue participation equity and recognition equity.